2015
DOI: 10.1177/0021998315601891
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of polyaniline, nanosilver, and carbon nanotube mixtures on the structure and properties of polyacrylonitrile composite nanofiber

Abstract: In this study, various amounts of carbon nanotubes (CNTs), nanosilver (AgNPs), and polyaniline (PANI) were incorporated at the same pot into the structure of composite polyacrylonitrile (PAN) nanofibers, which were produced by electrospinning process in order to see synergistic effect of the additives on the final properties of the composite materials. Performance and characteristic properties of composite nanofibers were analyzed by tensile tester, electrical conductivity meter, Fourier Transform Infrared Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…In our process, a certain amount of resin was poured onto the fabric and spread by a brush with very slight pressure. From the previous study, 39 it was found that the amount of CNT in the range of 1%-3% did not deteriorate the strength of composite polymer material. However, a high amount of CNT may improve the EMI-SE.…”
Section: Volumetric Electric Conductivitymentioning
confidence: 86%
“…In our process, a certain amount of resin was poured onto the fabric and spread by a brush with very slight pressure. From the previous study, 39 it was found that the amount of CNT in the range of 1%-3% did not deteriorate the strength of composite polymer material. However, a high amount of CNT may improve the EMI-SE.…”
Section: Volumetric Electric Conductivitymentioning
confidence: 86%
“…Pseudo first-order, pseudo second-order and external diffusion models were used to investigate the adsorption rate of methylene blue on PAN hard yarn waste/MWCNT-OH nanofibrous composite mat. Pseudo first-order kinetic equation is given in the following equation 28 :…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…The crystallinity of PAN/PANI/CNT composite nanofiber was higher than that of pure PAN, PAN/CNT, and PAN/PANI composite nanofibers [75]. Eren et al [76] incorporated various amounts of CNTs, AgNPs, and PANI into PAN nanofibers in order to see the synergistic effect of the additives on the final properties of the composite materials. Increase in the amount and types of additives generally resulted in an increase in the diameter of nanofibers and decrease in mechanical strength.…”
Section: Composite Pan Nanowebs With the Combined Addition Pani Cntsmentioning
confidence: 99%
“…Even though each of the nanoparticles was used in low concentrations, the composite nanowebs of PAN/1 wt% CNT/1 wt% AgNO 3 and PAN/ 3 wt% PANI/1 wt% AgNO 3 exhibited antimicrobial properties due to the synergistic effect of additives. It was suggested that PAN composite nanofibers with 3 wt% PANI and 1 wt% AgNO 3 generally presented better performance than the other samples in terms of electrical conductivity, antimicrobial activity, mechanical strength, crystallization, and thermal stability [76]. Kizildag et al [70] produced composite nanofibers from a solution of PAN, MWNTs, and AgNO 3 in DMSO by the electrospinning method.…”
Section: Composite Pan Nanowebs With the Combined Addition Pani Cntsmentioning
confidence: 99%